Aplicação do SERVQUAL e Analytic Hierarchy Process: ferramentas para melhoria dos serviços prestados pelo Hospital Universitário de Santa Maria, RS - Wegner, Roger da Silva (2016)
Public health is characterized by the importance of ensuring equitable and universal access to all Brazilian citizens, through quality and coverage procedures. Health is essential and necessary for a large portion of the population which is directly dependent on the services provided by the University Hospital of Santa Maria, for not having alternative access to private health plans. Public health is very relevant issue, in the area of administration resulting gains both for the organization in terms of excellence and also to society. The use of improvement tools is to contribute to the satisfaction of the customers regarding the services used. Given the above, this study aimed to evaluate the relationship between service quality and personnel management to improve the delivery of services at the University Hospital of Graphic Methods sector of Santa Maria (RS). The research was characterized as a case study being exploratory / descriptive with quantitative and qualitative approaches, using the SERVQUAL tool, 4 P's services (Profile, Process, Procedures and People) and AHP. Data were collected through a questionnaire to 294 patients and 26 employees. Through the analysis it was observed that, the organization needs to invest in human resources, since, according to the results obtained with the tools presented in the criterion 3 (Procedure) was the one that stood out, along with alternative training that had the highest degree of importance among the others, both in the perception of employees as well as the customer. Investment in alternative comes to help with employee performance and consequently for the development of the sector in relation to the services provided.